Impaired constitutive and regenerative neurogenesis in adult hyperglycemic zebrafish. Issue 3 (4th July 2016) - Dorsemans, Anne‐Claire; Soulé, Stéphanie; Weger, Meltem; Bourdon, Emmanuel; Lefebvre d'Hellencourt, Christian; Meilhac, Olivier; Diotel, Nicolas
Abstract: A growing body of evidence supports hyperglycemia as a putative contributor to several brain dysfunctions observed in diabetes patients, such as impaired memory capacity, neural plasticity, and neurogenic processes. Thanks to the persistence of radial glial cells acting as neural stem cells, the brain of the adult zebrafish constitutes a relevant model to investigate constitutive and injury‐induced neurogenesis in adult vertebrates. However, there is limited understanding of the impact of hyperglycemia on brain dysfunction in the zebrafish model. This work aimed at exploring the impact of acute and chronic hyperglycemia on brain homeostasis and neurogenesis. Acute hyperglycemia was shown to promote gene expression of proinflammatory cytokines ( il1β, il6, il8, and tnfα ) in the brain and chronic hyperglycemia to impair expression of genes involved in the establishment of the blood–brain barrier ( claudin 5a, zona occludens 1a and b ). Chronic hyperglycemia also decreased brain cell proliferation in most neurogenic niches throughout the forebrain and the midbrain. By using a stab wound telencephalic injury model, the impact of hyperglycemia on brain repair mechanisms was investigated. Whereas the initial step of parenchymal cell proliferation was not affected by acute hyperglycemia, later proliferation of neural progenitors was significantly decreased by chronic hyperglycemia in the injured brain of fish. Taken together, these data offer new evidence highlighting the evolutionary conserved adverse effects of hyperglycemia on neurogenesis and brain healing in zebrafish. In addition, our study reinforces the utility of zebrafish as a robust model for studying the effects of metabolic disorders on the central nervous system. J. Comp. Neurol. 525:442–458, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Using a model of chronic hyperglycemia in zebrafish, the authors showed that (1) hyperglycemia results in a decreased brain cell proliferation under homeostatic conditions and that (2) injury‐induced neurogenesis is impaired. These data highlight the adverse effects of hyperglycemia in brain homeostasis.